Solution-enhanced dispersion by supercritical carbon dioxide in production of Andrographis paniculata (Burm.f.) Wall. ex Nees powder - Lee, Sin Yee (2018)
Andrographolide with poor aqueous solubility and poor dissolution rate is predisposed to low oral bioavailability. To overcome these constraints, strategies (reducing crystallinity and increasing surface area) were employed through Solution-Enhanced Dispersion by Supercritical Carbon Dioxide (SEDS). SEDS precipitation of Andrographis paniculata (Burm.f.) Wall. ex Nees extract from CO2-Acetone and CO2- Acetone:Ethanol (v/v) 1:1 systems at different pressure (100, 150 bar) and temperature (40, 50 ̊C) combination as well as aqueous solubility of andrographolide precipitated were first studied. Modification of its aqueous solubility was then conducted by manipulating precipitation using CO2-Acetone:Ethanol (v/v) of different proportions at selected pressure-temperature combination. Results showed that the low crystalline A. paniculata extract powder precipitated from CO2-Acetone system at 150 bar, 40 ̊C had the highest aqueous solubility of andrographolide (0.06 mg/mL), a two-fold increment than extract. However, absorption of andrographolide could still be poor for its low dissolution rate in Simulated Intestinal Fluid (SIF), pH 7.4 (0.06 mg/mL release in 90 min). Therefore, SEDS co-precipitation of A. paniculata with polymers were conducted using the best SEDS precipitation parameters (150 bar, 40 ̊C, CO2-Acetone system). SEDS co-precipitated A. paniculata with Pluronic F127 or Eudragit EPO exhibited poorer andrographolide dissolution in SIF (< 0.03 mg/mL release in 90 min). SEDS coprecipitated A. paniculata with Eudragit L100-55 in Eudragit L100-55:A. paniculata mass ratio (2:25) showed improved dissolution rate of andrographolide in SIF (0.06 mg/mL release in 45 min) and mass ratio increment to 6:25 resulted in higher andrographolide release and dissolution rate (0.09 mg/mL release in 30 min). Only 20- 30% of andrographolide from SEDS co-precipitates (6:25) was degraded after twomonth storage whereas 30-60% of andrographolide was degraded after addition into beverages in a day. Since acetone content in SEDS co-precipitates (6:25) was < 0.1 ppm, its increased brine shrimp cytotoxicity (LC50 = 46.46 μg/mL) could be attributed to higher aqueous solubility and dissolution rate of andrographolide.